Semantic Web Technologies for Classification and Indexing of E-government Archive (The International Journal of Engineering & Information Technology (IJEIT), 2016)
Semantic web Meta data and natural languageprocessing technologies can be combined to produce systems that working more efficiently for classification and retrievalof documents. The main aim of this Paper is applyingsemantic web technologies and tools for indexing,classifying, and retrieving Arabic content documents withinE-government archive by using semantic web annotation technology and natural language processing (NLP).